Greening hotels: does motivating hotel employees promote in-role green performance? The role of culture. Issue 4 (3rd April 2023) - Pham, Nhat Tan; Chiappetta Jabbour, Charbel Jose; Vo-Thanh, Tan; Huynh, Toan Luu Duc; Santos, Clarice
Abstract: In the new global economy, environmentally friendly policies have become a central issue for firms. The increasing attention given to the benefits of those policies has prompted research on the development of environmental management systems that encourage employees to engage in environmental activities. However, there is limited evidence concerning the relationship between employee motivation and employees' in-role green performance, in addition to the potential impact of culture and organizational citizenship behavior for the environment. Through a quantitative study of 301 managerial and non-managerial employees working in three- to five-star hotels, this study makes a major contribution by demonstrating that practices aimed at motivating hotel employees (e.g. green reward and performance management) are significantly linked with employees' in-role green performance and organizational citizenship behavior for the environment. The findings also indicate that the influence of green rewards on employees' in-role green performance and organizational citizenship behaviors for the environment is stronger when hotels are managed by Western corporations. Conversely, the study showed that the effect of green performance management on these two dependent variables is not moderated by culture. This article supports efforts to widen national cultural perspectives in the development and application of green human resource management.